A method for preparing modified graphite negative electrode material for lithium ion battery
Through multiple coating technology and pickling treatment, the graphite negative electrode material of lithium-ion battery with a mesh structure is formed, which solves the problem of uneven coating layer in natural graphite modification and improves the cycle life and fast charging performance of the battery.
Patent Information
- Application Number
- CN202411288217.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-14
AI Technical Summary
In the prior art, it is difficult to form a uniform cladding layer during the modification process of natural graphite, resulting in limited cycle life and fast charging capability of lithium-ion batteries.
Using multiple coating technology, the natural graphite is first coated with asphalt and carbonized, and then the surface is coated with starch solution. A uniform secondary coating layer is formed by carbonization at high temperature, and metal oxide is removed during the pickling process to form A mutually weaving pore structure is used to improve interface stability.
It significantly improves the uniformity of the cladding layer and the stability of the physical structure, and improves the cycle life and fast charging capability of lithium-ion batteries.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary battery material preparation, and more specifically, relates to a method for preparing a modified lithium-ion battery graphite negative electrode material. Background Art
[0002] Due to factors such as its physical structure compared to artificial graphite, natural graphite cannot be used directly as a negative electrode material for lithium-ion batteries without modification. If used directly, it will significantly affect the cycle life or fast charging capability of the lithium-ion battery.
[0003] Among the existing modification technologies, coating treatment is a common method of modification. For example, asphalt is used for coating. This type of coating treatment has a common problem, that is, it is difficult to evenly coat the surface of natural graphite particles with a coating layer, which leads to an unstable physical structure of the product. During long-term use, the surface coating layer is also prone to gradually fall off as the volume of the material changes, and the product cycle life ends. Summary of the invention
[0004] The technical problem to be solved by the present invention is: in view of the problem that it is difficult to form a uniform coating layer on the surface of conventional natural graphite during the modification process, thereby affecting the service life of the product, the present invention provides a method for preparing a modified lithium ion battery graphite negative electrode material.
[0005] The purpose of the present invention is to provide a method for preparing a modified graphite negative electrode material for a lithium ion battery.
[0006] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0007] A method for preparing a modified graphite negative electrode material for a lithium ion battery, characterized in that the specific preparation steps include:
[0008] After dissolving and dispersing the asphalt and the solvent, adding the spherical natural graphite and the first nano-metal oxide, and mixing to obtain a suspension;
[0009] The temperature of the first high temperature carbonization is 800-820°C;
[0010] The primary coated natural graphite, the second nano metal oxide and the starch solution are mixed, sprayed and granulated, and then subjected to a second high-temperature carbonization and dispersion to obtain a secondary coated natural graphite; the second high-temperature carbonization temperature is 1080-1120°C;
[0011] The secondary coated natural graphite is ultrasonically pickled to remove the first nano-metal oxide and the second nano-metal oxide, and then washed with water and dried to obtain a modified lithium ion battery graphite negative electrode material.
[0012] Preferably, the D50 of the spherical natural graphite is 10-12 μm; and the D50 of the first nano-metal oxide is 3-5 nm, and the D50 of the second nano-metal oxide is 12-15 nm.
[0013] Preferably, the first nano-metal oxide is selected from any one of nano-aluminum oxide, nano-zinc oxide, nano-magnesium oxide and nano-iron oxide.
[0014] Preferably, the second nano-metal oxide is selected from any one of nano-aluminum oxide, nano-zinc oxide, nano-magnesium oxide and nano-iron oxide.
[0015] Preferably, the mass ratio of the asphalt to the solvent is 1:10-12; the mass ratio of the spherical natural graphite to the asphalt is 2.2-2.5:1; and the amount of the first nano-metal oxide is 6.5-7.5% of the mass of the spherical natural graphite.
[0016] Preferably, the amount of the second nano-metal oxide is 0.5-0.6 times the mass of the first nano-metal oxide.
[0017] Preferably, the solvent is selected from any one of tetrahydrofuran, n-hexane, xylene, carbon disulfide or carbon tetrachloride.
[0018] Preferably, the specific preparation step further comprises: when preparing the suspension, adding single-walled carbon nanotubes in an amount of 0.1-0.2% by mass of the spherical natural graphite.
[0019] Preferably, the average length of the single-walled carbon nanotubes is 200-220 nm.
[0020] Preferably, the surface of the single-walled carbon nanotube is coated with a silane coupling agent, and the silane coupling agent is selected from any one of silane coupling agent KH-550, silane coupling agent KH-560 or silane coupling agent KH-570.
[0021] The present invention first dissolves and disperses asphalt and then uses it to coat spherical natural graphite. However, since asphalt is generally difficult to fully dissolve and its relative viscosity after dissolution is relatively large, it is difficult to wet and spread it completely and evenly on the surface of natural graphite. In addition, during the high-temperature carbonization process, the asphalt will also soften and be secondary distributed, which will cause the coating layer on the surface of natural graphite to be uneven. Therefore, the present invention adopts multiple coatings to solve this technical problem. After the asphalt is coated and carbonized, a layer of starch solution is coated on its surface. After carbonization, the surface properties of natural graphite change and it will have better affinity for starch solution. Therefore, the starch solution can be evenly wetted and spread during the spray drying process, and it will not be like asphalt during the carbonization process. There is a softening and flowing process, so after the secondary carbonization coating, the uniformity of the surface coating layer can be significantly improved; and, because the starch is dissolved, its molecular chain is fully stretched, and it can partially penetrate and diffuse into the pores of the coating layer formed by the carbonization of the asphalt. With the subsequent carbonization, the second coating layer can be interlocked with the first coating layer, effectively improving the physical structure stability of the interface between the two. However, the inventors found that if the temperature is controlled to be relatively low during the carbonization of the asphalt so that it is not completely carbonized, and then the temperature is raised to a higher temperature after the starch is coated, so that the asphalt and starch are carbonized at a higher temperature, the bonding interface between the two can become stronger, and it is easy to form a continuous mass transfer channel to avoid blockage of the mass transfer channel at the interface.
[0022] Furthermore, by adding a first nano-metal oxide to the asphalt and a second nano-metal oxide to the starch solution, there is a certain difference in particle size between the two, specifically, the particle size of the first nano-metal oxide is smaller than that of the second nano-metal oxide; and in the subsequent pickling process, both are removed by pickling dissolution, so that the physical space originally occupied by them is converted into a mass transfer channel, and it is avoided that the two carbonized layers accumulate and block the channel during multiple coating processes. In this way, a mass transfer channel with relatively large pores can be formed in the carbonized layer formed by starch, and a mass transfer channel with relatively small pores can be formed in the carbonized layer formed by asphalt. In this way, it is not only beneficial to the absorption of the electrolyte, but also beneficial to the rapid absorption of lithium ions during fast charging; more importantly, it is also beneficial to the stability of the physical structure of the surface coating layer, so that the product has a better cycle life;
[0023] Furthermore, by adding a certain amount of single-walled carbon nanotubes and adding them to the suspension, a coating layer is formed together with the asphalt. In this process, the single-walled carbon nanotubes can improve the electrical conductivity, thermal conductivity, and physical structure strength of the coating layer formed by the asphalt; wherein the thermal conductivity is helpful for the second heating and carbonization after the starch coating. Specifically, it can help the heat to be transferred quickly and evenly to the inside, so that it can be evenly heated and carbonized, avoiding local overheating and causing uneven physical structure; moreover, since the coating layer formed by the asphalt is in direct contact with natural graphite, during the use of the product, the volume change of natural graphite will be directly transferred to the coating layer. Therefore, the presence of single-walled carbon nanotubes can improve its ability to cope with the volume change of natural graphite to a certain extent, thereby ensuring the structural stability of the product after long-term circulation. DETAILED DESCRIPTION
[0024] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0025] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0026] Example 1
[0027] Asphalt and solvent were mixed in a mass ratio of 1:10 and added into the reactor. Then, in a closed environment, at a temperature of 140°C and a shear rate of 5500 r / min, stirring and shearing dispersion was continued for 4 hours, and then cooled and discharged to obtain a dispersion.
[0028] Adding spherical natural graphite, single-walled carbon nanotubes and a first nano-metal oxide to the dispersion in sequence, and then continuously stirring and mixing for 80 minutes at a stirring speed of 1000 r / min to obtain a suspension;
[0029] Wherein, the mass ratio of the spherical natural graphite to the asphalt is 2.2:1; the amount of the first nano-metal oxide is 6.5% of the mass of the spherical natural graphite;
[0030] The solvent is selected from tetrahydrofuran;
[0031] The D50 of the spherical natural graphite is 10 μm; and the D50 of the first nano-metal oxide is 3 nm; the first nano-metal oxide is selected from: nano-aluminum oxide;
[0032] The amount of the single-walled carbon nanotubes is 0.1% of the mass of the spherical natural graphite;
[0033] The average length of the single-walled carbon nanotubes is 200 nm.
[0034] The surface of the single-walled carbon nanotube is coated with a silane coupling agent, and the silane coupling agent is selected from silane coupling agent KH-550;
[0035] The suspension is evaporated to remove the solvent, and then transferred into a carbonization furnace, heated to 800°C at a rate of 4°C / min in an argon atmosphere, and carbonized for 3 hours, then cooled to room temperature with the furnace, discharged, crushed, and sieved to obtain a primary coated natural graphite with a D50 of 12 μm;
[0036] The primary coated natural graphite, the second nano metal oxide and the starch solution are mixed, sprayed and granulated, and then transferred into a carbonization furnace, heated to 1080°C at a rate of 4°C / min in an argon atmosphere, and carbonized for 3 hours, then cooled to room temperature with the furnace, and then dispersed to obtain the secondary coated natural graphite;
[0037] The amount of the second nano-metal oxide is 0.5 times the mass of the first nano-metal oxide; the D50 of the second nano-metal oxide is 12nm; the second nano-metal oxide is selected from: nano-aluminum oxide;
[0038] The mass fraction of the starch solution is 10%; and the amount of the starch solution is 8.5 times the total mass of the primary coated natural graphite and the second nano metal oxide;
[0039] The secondary coated natural graphite and a hydrochloric acid solution with a mass fraction of 8% are mixed in a mass ratio of 1:10, and ultrasonic pickling is performed for 45 minutes at an ultrasonic frequency of 80 kHz and a temperature of 55° C., and then filtered, and the filter cake is washed with deionized water until the washing liquid is neutral, and the washed filter cake is transferred to an oven for drying to obtain a modified lithium ion battery graphite negative electrode material.
[0040] Example 2
[0041] Asphalt and solvent were mixed in a mass ratio of 1:11, added into the reactor, and then in a closed environment, at a temperature of 145°C and a shear rate of 5800 r / min, continuously stirred and sheared for 5 hours, cooled, discharged, and obtained a dispersion;
[0042] Adding spherical natural graphite, single-walled carbon nanotubes and the first nano-metal oxide to the dispersion in sequence, and then continuously stirring and mixing for 90 minutes at a stirring speed of 1100 r / min to obtain a suspension;
[0043] Wherein, the mass ratio of the spherical natural graphite to the asphalt is 2.3:1; the amount of the first nano-metal oxide is 6.8% of the mass of the spherical natural graphite;
[0044] The solvent is selected from n-hexane;
[0045] The D50 of the spherical natural graphite is 11 μm; and the D50 of the first nano-metal oxide is 4 nm; the first nano-metal oxide is selected from: nano-zinc oxide;
[0046] The single-walled carbon nanotubes are used in an amount of 0.15% of the mass of the spherical natural graphite;
[0047] The average length of the single-walled carbon nanotubes is 210 nm.
[0048] The surface of the single-walled carbon nanotube is coated with a silane coupling agent, and the silane coupling agent is selected from silane coupling agent KH-560;
[0049] The suspension is evaporated to remove the solvent, and then transferred into a carbonization furnace, heated to 810°C at a rate of 5°C / min in an argon atmosphere, and carbonized for 3.5 hours, then cooled to room temperature with the furnace, discharged, crushed, and sieved to obtain a primary coated natural graphite with a D50 of 12 μm;
[0050] The primary coated natural graphite, the second nano metal oxide and the starch solution are mixed, sprayed and granulated, and then transferred into a carbonization furnace, heated to 1090°C at a rate of 5°C / min in an argon atmosphere, and carbonized for 3.5 hours, then cooled to room temperature with the furnace, and then dispersed to obtain the secondary coated natural graphite;
[0051] The amount of the second nano-metal oxide is 0.55 times the mass of the first nano-metal oxide; the D50 of the second nano-metal oxide is 13 nm; the second nano-metal oxide is selected from: nano-aluminum oxide;
[0052] The mass fraction of the starch solution is 11%; and the amount of the starch solution is 8.5 times the total mass of the primary coated natural graphite and the second nano metal oxide;
[0053] The secondary coated natural graphite and a hydrochloric acid solution with a mass fraction of 9% are mixed in a mass ratio of 1:10, and ultrasonic pickling is performed for 50 minutes at an ultrasonic frequency of 88 kHz and a temperature of 56°C. The mixture is filtered, and the filter cake is washed with deionized water until the washing liquid is neutral. The washed filter cake is then transferred to an oven for drying to obtain a modified lithium-ion battery graphite negative electrode material.
[0054] Example 3
[0055] Asphalt and solvent were mixed in a mass ratio of 1:12, added into the reactor, and then stirred and sheared for 6 hours in a closed environment at a temperature of 150°C and a shear rate of 6000 r / min, and then cooled and discharged to obtain a dispersion;
[0056] Adding spherical natural graphite, single-walled carbon nanotubes and a first nano-metal oxide to the dispersion in sequence, and then continuously stirring and mixing for 100 minutes at a stirring speed of 1200 r / min to obtain a suspension;
[0057] Wherein, the mass ratio of the spherical natural graphite to the asphalt is 2.5:1; the amount of the first nano-metal oxide is 7.5% of the mass of the spherical natural graphite;
[0058] The solvent is selected from xylene;
[0059] The D50 of the spherical natural graphite is 12 μm; and the D50 of the first nano-metal oxide is 5 nm; the first nano-metal oxide is selected from: nano-magnesium oxide;
[0060] The amount of the single-walled carbon nanotubes is 0.2% of the mass of the spherical natural graphite;
[0061] The average length of the single-walled carbon nanotubes is 220 nm.
[0062] The surface of the single-walled carbon nanotube is coated with a silane coupling agent, and the silane coupling agent is selected from silane coupling agent KH-570;
[0063] The suspension is evaporated to remove the solvent, and then transferred into a carbonization furnace, heated to 820° C. at a rate of 6° C. / min in an argon atmosphere, and carbonized for 4 hours, then cooled to room temperature with the furnace, discharged, crushed, and sieved to obtain a primary coated natural graphite with a D50 of 13 μm;
[0064] The primary coated natural graphite, the second nano metal oxide and the starch solution are mixed, sprayed and granulated, and then transferred into a carbonization furnace, heated to 1120°C at a rate of 6°C / min in an argon atmosphere, and carbonized for 4 hours, then cooled to room temperature with the furnace, and then dispersed to obtain the secondary coated natural graphite;
[0065] The amount of the second nano-metal oxide is 0.6 times the mass of the first nano-metal oxide; the D50 of the second nano-metal oxide is 15 nm; the second nano-metal oxide is selected from: nano zinc oxide;
[0066] The mass fraction of the starch solution is 12%; and the amount of the starch solution is 8.5 times the total mass of the primary coated natural graphite and the second nano metal oxide;
[0067] The secondary coated natural graphite and a hydrochloric acid solution with a mass fraction of 8-10% are mixed in a mass ratio of 1:10, and ultrasonic pickling is performed for 60 minutes at an ultrasonic frequency of 90 kHz and a temperature of 60°C. The mixture is filtered, and the filter cake is washed with deionized water until the washing liquid is neutral. The washed filter cake is then transferred to an oven for drying to obtain a modified lithium ion battery graphite negative electrode material.
[0068] Example 4
[0069] The present embodiment differs from the embodiment 1 in that no single-walled carbon nanotubes are added, and the other conditions remain unchanged.
[0070] Example 5
[0071] Asphalt and solvent were mixed in a mass ratio of 1:10 and added into the reactor. Then, in a closed environment, at a temperature of 140°C and a shear rate of 5500 r / min, stirring and shearing dispersion was continued for 4 hours, and then cooled and discharged to obtain a dispersion.
[0072] Adding spherical natural graphite and the first nano metal oxide to the dispersion in sequence, and then continuously stirring and mixing for 80 minutes at a stirring speed of 1000 r / min to obtain a suspension; (no single-walled carbon nanotubes are added at this time);
[0073] Wherein, the mass ratio of the spherical natural graphite to the asphalt is 2.2:1; the amount of the first nano-metal oxide is 6.5% of the mass of the spherical natural graphite;
[0074] The solvent is selected from tetrahydrofuran;
[0075] The D50 of the spherical natural graphite is 10 μm; and the D50 of the first nano-metal oxide is 3 nm; the first nano-metal oxide is selected from: nano-aluminum oxide;
[0076] The suspension is evaporated to remove the solvent, and then transferred into a carbonization furnace, heated to 800°C at a rate of 4°C / min in an argon atmosphere, and carbonized for 3 hours, then cooled to room temperature with the furnace, discharged, crushed, and sieved to obtain a primary coated natural graphite with a D50 of 12 μm;
[0077] The primary coated natural graphite, the second nano metal oxide, the single-walled carbon nanotube and the starch solution are mixed, sprayed and granulated, and then transferred into a carbonization furnace, heated to 1080°C at a rate of 4°C / min in an argon atmosphere, and carbonized for 3 hours, then cooled to room temperature with the furnace, and then dispersed to obtain the secondary coated natural graphite;
[0078] The amount of the single-walled carbon nanotubes is 0.1% of the mass of the spherical natural graphite;
[0079] The average length of the single-walled carbon nanotubes is 200 nm.
[0080] The surface of the single-walled carbon nanotube is coated with a silane coupling agent, and the silane coupling agent is selected from silane coupling agent KH-550;
[0081] The amount of the second nano-metal oxide is 0.5 times the mass of the first nano-metal oxide; the D50 of the second nano-metal oxide is 12nm; the second nano-metal oxide is selected from: nano-aluminum oxide;
[0082] The mass fraction of the starch solution is 10%; and the amount of the starch solution is 8.5 times the total mass of the primary coated natural graphite and the second nano metal oxide;
[0083] The secondary coated natural graphite and a hydrochloric acid solution with a mass fraction of 8% are mixed in a mass ratio of 1:10, and ultrasonic pickling is performed for 45 minutes at an ultrasonic frequency of 80 kHz and a temperature of 55° C., and then filtered, and the filter cake is washed with deionized water until the washing liquid is neutral, and the washed filter cake is transferred to an oven for drying to obtain a modified lithium ion battery graphite negative electrode material.
[0084] Comparative Example 1
[0085] The difference between this comparative example and Example 1 is that the first nano-metal oxide and the second nano-metal oxide are not added, and the other conditions remain unchanged.
[0086] Comparative Example 2
[0087] The difference between this comparative example and Example 1 is that the first nano-metal oxide is not added, and the other conditions remain unchanged.
[0088] Comparative Example 3
[0089] The difference between this comparative example and Example 1 is that the second nano-metal oxide is not added, and the other conditions remain unchanged.
[0090] Comparative Example 4
[0091] The difference between this comparative example and Example 1 is that the D50 of the first nano-metal oxide and the second nano-metal oxide are both 3 nm, and the other conditions remain unchanged.
[0092] Comparative Example 5
[0093] The difference between this comparative example and Example 1 is that the temperature of the two high-temperature carbonizations is 1080° C., and the other conditions remain unchanged.
[0094] The performance tests were performed on the products obtained in the above embodiments and comparative examples. The specific test methods and test results are as follows:
[0095] The products obtained in each embodiment or comparative example were mixed with conductive carbon black and polyvinylidene fluoride binder in a mass ratio of 8:1:1, and N-methylpyrrolidone was added. After grinding, they were coated on the surface of a copper foil with a thickness of 6 μm, and dried as a working electrode;
[0096] Metal lithium sheet, working electrode, PP separator, 1 mol / L LiPF6 electrolyte (solvent is a mixture of ethylene carbonate, diethyl carbonate, ethyl methyl carbonate in a volume ratio of 1:1:1) are assembled into a CR2032 button battery, and the battery assembly is carried out in a glove box filled with argon protection;
[0097] The button cell was tested for charge, discharge and cycle performance using a LAND test system (LAND CT2001A). The voltage test range was 0.01-3.0V. For the same example or comparative example product, multiple groups of tests were conducted. The charge and discharge current densities were adjusted to 0.2C and 0.6C, respectively. After 300 cycles of charge and discharge, the capacity retention rate of each battery was tested. The specific test results are shown in Table 1.
[0098] Table 1: Product performance test results
[0099] Capacity retention rate / %0.2C Capacity retention rate / %0.6C Example 1 94.2% 90.1% Example 2 94.5% 90.3% Example 3 94.3% 90.2% Example 4 91.1% 86.9% Example 5 92.2% 88.1% Comparative Example 1 82.1% 75.6% Comparative Example 2 85.6% 78.3% Comparative Example 3 86.1% 79.4% Comparative Example 4 88.1% 82.5% Comparative Example 5 89.2% 83.3%
[0100] It can be seen from the test results in Table 1 that the product obtained by the present invention has relatively better cycle performance, and after the charging rate is increased, its cycle life is also relatively better maintained.
[0101] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a modified graphite negative electrode material for a lithium ion battery, characterized in that: The specific preparation steps include: After dissolving and dispersing the asphalt and the solvent, adding the spherical natural graphite and the first nano-metal oxide, and mixing to obtain a suspension; The suspension is subjected to solvent evaporation, first high-temperature carbonization, crushing and screening in sequence to obtain primary coated natural graphite; the temperature of the first high-temperature carbonization is 800-820° C.; The primary coated natural graphite, the second nano metal oxide and the starch solution are mixed, sprayed and granulated, and then subjected to a second high-temperature carbonization and dispersion to obtain a secondary coated natural graphite; the second high-temperature carbonization temperature is 1080-1120°C; The secondary coated natural graphite is ultrasonically acid washed to remove the first nano-metal oxide and the second nano-metal oxide, and then washed with water and dried to obtain a modified lithium-ion battery graphite negative electrode material; The D50 of the spherical natural graphite is 10-12 μm; the D50 of the first nano-metal oxide is 3-5 nm, and the D50 of the second nano-metal oxide is 12-15 nm.
2. The method for preparing a modified lithium ion battery graphite negative electrode material according to claim 1, characterized in that: The first nano-metal oxide is selected from any one of nano-aluminum oxide, nano-zinc oxide, nano-magnesium oxide, and nano-iron oxide.
3. The method for preparing a modified lithium ion battery graphite negative electrode material according to claim 1, characterized in that: The second nano-metal oxide is selected from any one of nano-aluminum oxide, nano-zinc oxide, nano-magnesium oxide, and nano-iron oxide.
4. The method for preparing a modified lithium ion battery graphite negative electrode material according to claim 1, characterized in that: The mass ratio of the asphalt to the solvent is 1:10-12; the mass ratio of the spherical natural graphite to the asphalt is 2.2-2.5:1; and the amount of the first nano-metal oxide is 6.5-7.5% of the mass of the spherical natural graphite.
5. The method for preparing a modified lithium ion battery graphite negative electrode material according to claim 4, characterized in that: The amount of the second nano-metal oxide is 0.5-0.6 times the mass of the first nano-metal oxide.
6. The method for preparing a modified lithium ion battery graphite negative electrode material according to claim 1, characterized in that: The solvent is selected from any one of tetrahydrofuran, n-hexane, xylene, carbon disulfide or carbon tetrachloride.
7. The method for preparing a modified lithium ion battery graphite negative electrode material according to claim 1, characterized in that: The specific preparation steps also include: when preparing the suspension, adding single-walled carbon nanotubes in an amount of 0.1-0.2% by weight of the spherical natural graphite.
8. The method for preparing a modified lithium-ion battery graphite negative electrode material according to claim 7, characterized in that: The average length of the single-walled carbon nanotubes is 200-220 nm.
9. The method for preparing a modified lithium-ion battery graphite negative electrode material according to claim 7, characterized in that: The surface of the single-walled carbon nanotube is coated with a silane coupling agent, and the silane coupling agent is selected from any one of silane coupling agent KH-550, silane coupling agent KH-560 or silane coupling agent KH-570.